Neurology : a Clinician's Approach - Tarulli, Andrew (Cambridge medicine (Series), 2011)
"Neurology: A Clinician's Approach teaches a symptom-oriented approach to the 20 most common problems which face neurologists in training. Emphasizing the primary importance of the patient history, the reader is instructed which questions to ask in order to elicit the chief complaint, how to ask these questions, and how to interpret the answers. The neurologic examination is presented as a flexible diagnostic tool rather than as a rigid exercise to be performed by rote and without reference to the chief complaint. Each chapter integrates evidence-based and experience-based approaches to diagnostic testing and treatment. Frequently-encountered conditions, uncommon 'zebras', and non-neurologic mimics of nervous system dysfunction are all given appropriate weight. Neurology: A Clinician's Approach is essential reading for neurologists in training, including neurology residents and medical students"--Provided by publisher